Retinoid Therapy in a Case of Harlequin Ichthyosis with a Short Literature Review - Emad Bahashwan; Jaber Alfaifi; Sahar Elmaghawri Mohamed Moursi; Youssef Elbayoumi Soliman (Case Reports in Dermatological Medicine)
Harlequin ichthyosis (HI) is a genetically inherited epidermal disorder due to the mutation of the ABCA12 gene, which is responsible for lipid transportation, and presents with large keratinised scales characterised by deep erythematous fissures, with ectropion and eclabium. A moderate number of cases and a high mortality rate have been recorded. In this case report, a pregnant lady gave birth to a 33-week-old premature foetus with characteristic symptoms of HI. After admitting him to the NICU, a multidisciplinary treatment approach was conducted with paediatric dermatologists, ophthalmologists, urologists, and dieticians. The prognosis is positive, with desquamation of the hyperkeratotic plate revealing an erythematous and shiny skin. A short literature review on HI characteristics, diagnostic aids, and management has also been added.